Writing prescriptions by nurses and midwives – legal status in Poland and general review of the international situation - Bartosiewicz, Anna; Binkowska-Bury, Monika; Januszewicz, Paweł (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of this paper is to demonstrate a current legal status in Poland in reference to expanding the scope of practice of nurses and midwives to writing prescriptions. According to the new regulations, nurses and midwives will be able to write prescriptions from 1 January 2016 on the basis of a bill motioned by the government. Additionally, there was included a brief characteristic of experience of other countries in that matter. The functioning of the system of writing prescriptions by nurses has been discussed based on example of 10 countries: Ireland, Great Britain, the Netherlands, Sweden, The United States, Botswana, Australia, New Zealand, Canada and Republic of South Africa. Positive experience of other countries in this subject may serve as an example for creating and developing such solutions in Poland.